Tourists Expenditure Multipliers: What Difference do Financing Sources Play? - Eduardo Haddad; Alexandre Porsse; Wilson Rabahy (European Regional Science Association (ERSA), 2011)
This paper analyses the consumption patterns of tourists coming from different domestic origins and choosing other domestic destinations in Brazil, in terms of expenditure level and composition. We also look at different alternative of financing tourist expenditures and their implications for the net multipliers in an integrated framework. We use survey data for domestic tourism in Brazil to consolidate an interstate matrix of expenditures by tourists. We then use an interregional input-output system for Brazil to compute the tourism multipliers based on alternative hypotheses for the sources of financing of expenditures by tourists: (i) equivalent reductions in consumption in the respective origin regions, representing an induced substitution effect in the consumption basket of travelers; and (ii) reduction in personal savings, maximizing the multiplier effects of expenditures. The results are analyzed and its implications for regional inequality in the country are discussed.
Keywords: 330